Molecular Dynamics Study of Human MTHFR Wild-Type and A222V Mutant-Type: A Computational Approach - Michael Resta Surya Yanuar; Dita Maria Virginia; Enade Perdana Istyastono (Sanata Dharma University, 2023)
Methylenetetrahydrofolate reductase (MTHFR) is an essential enzyme for the homeostasis and metabolism of intracellular folate. However, it is known that one of the commonly found MTHFR gene SNPs (A222V) causes a decrease in activity which decreases folate levels and increases the accumulation of homocysteine in the blood. The purpose of this study was to investigate the molecular dynamics of MTHFR wild-type protein and MTHFR A222V mutant protein in silico. After some preparations, the crystal structure of MTHFR with code 6FCX obtained from the Protein Data Bank was used as the input file for molecular dynamics (MD) simulations. YASARA-Structure was employed for performing 50 ns production run of MD simulations. The deviation of the root-mean-squared deviation value of the backbone atoms (∆RMSDBb) of MTHFR wild-type is consistently less than 2 Å from the beginning of the MD simulations production runs. On the other hand, there is a sudden spike of ∆RMSDBb of MTHFR A222V from 15.01 to 20.00 ns of 2.221 Å. According to the analysis of ∆RMSDBb, MTHFR wild-type protein is considered stable and the MTHFR A222V mutant protein is considered unstable which may lead to various clinical problems for the person possessing this mutation.